One-step hydrothermal synthesis of 2D WO3 nanoplates@ graphene nanocomposite with superior anode performance for lithium ion battery. (1st August 2019) - Dang, Wei; Wang, Wei; Yang, Yun; Wang, Yang; Huang, Jie; Fang, Xiong; Wu, Liping; Rong, Zhihao; Chen, Xi; Li, Xing; Huang, Liuchun; Tang, Xincun
Abstract: The WO3 nanosheet@reduced graphene oxide (WO3 nanosheet@rGO) square particles have been synthesized successfully by a hydrothermal method. The structure and polymorphy of the particle are well characterized by XRD, FT-IR, XPS, SEM, TEM, HRTEM, Raman spectra and BET analysis. The electrochemical behaviors are researched by using CV, galvanostatic cycle and EIS. The results indicate that the special combination about the two-dimension WO3 nanoplate and graphene scales can promote the electrochemical properties of the metallic oxide effectively. Compared with the pure WO3, a higher initial discharge capacity of the WO3 nanosheet@rGO composite is 1143 mA h g −1, the reversible capacity can also maintain in 1005.7 mA h g −1 after 150 cycles in the condition of 100 mA g −1 and 0.01–3 V. The outstanding electrochemical performances composite demonstrates that WO3 nanosheet@rGO synthesized by this method is feasible and could be used as a promising anode material for LIBs. Graphical abstract: Image 1 Highlights: The combination of 2D WO3 nanosheet and graphene at different points reduces the reunion in some degree by a simple hydrothermal method. The WO3 nanosheet@rGO remains a high discharge specific capacity of 1005.7 mA h g −1 after 150 cycles at 100 mA g −1 . Incorporating highly conductive the graphene into a 2D nanostructure to enhance the fast charge transfer and a long-term cyclability.